(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2024)
Background: The novel coronavirus SARS-CoV-2 is a newly emerging virus. Positive detection of SARS-CoV-2 RNA by RT-PCR has been used to confirm SARS-CoV-2 infection. Recently positive detection of IgG and IgM antibodies specific to SARS-CoV-2 has also been recognized as deterministic evidence for confirmed SARS-CoV-2 infection. The antibody response in COVID-19 patient remains largely unknown, and the clinical values of antibody testing have not been fully demonstrated. Objective: To better clarify the humoral immune response during SARS-CoV-2 infection. Methods: This cross sectional study was carried out on 200 RT-PCR confirmed COVID-19 cases. For better evaluation of antibody response, patients were divided into two groups, group I and group II, each consisting of 100 persons. Results: Out of a total 200 cases antibody was detected in 104(52%) cases and antibody not detected in 96(48%) cases. Out of 104 seropositive cases only IgG was detected in 69.2% cases, only IgM in 10.6% cases and both IgG, IgM in 20.2% cases.In group I seropositivity was 68%. IgG, IgM and both IgG, IgM positivity were 58.8%, 14.7% and 26.5% respectively. In group II seropositivity was 36 %. Positivity for IgG, IgM and both IgG, IgM were 88.9%, 2.8% and 8.3% respectively. Conclusion: As we learn more about the long-term implications of COVID-19 on recovered individuals, antibody tests can be used to increase this understanding of the immune system response to SARS-CoV-2, quantify the magnitude of the COVID-19 outbreak and effectively manage patients. JAFMC Bangladesh, Vol 19, No 2 (December) 2023: 3-6